Analisis Pengembangan E-Government di Kota Salatiga - Lestari, Sinta Denna; Widowati, Nina (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
The development of e-Government is one of the efforts undertaken by the government in improving the quality of service and relationships between the citizen, business, and government. E-Government is intended to support good governance through the use of technology that will facilitate the public in accessing information. The method used in this research is descriptive qualitative method. The purpose of this study is to describe and analyze the development of e-Government in Salatiga City and to know the obstacles in the development of e-Government in Salatiga City. The results show that the development of e-Government in Salatiga City has not been in accordance with what is expected. This can be proved from the three elements, two of the elements are the support and capacity elements have not supported in the development of e-Government, while one element that is the value already supports. Constraints faced in the development of e-Government is the absence of local regulations and the decisions of the mayor governing of e-Government in the Salatiga City, the lack of socialization conducted directly bring together the Salatiga City government and the citizen, and lack of budget, infrastructure and human resources in the implementation of e-Government in Salatiga City. Recommendation for this research is required of law product in the form of local regulation and also mayor decision as base in applying of e-Government in Salatiga City, need of socialization about utilization of IT in government environment and for society, need existence of improvement of facility and infrastructure of e-Government and the addition of human resources.